PENGARUH METODE PEMBELAJARAN SOSIODRAMA TERHADAP KREATIVITAS BELAJAR SISWA KELAS XI PADA MATA PELAJARAN BAHASA INDONESIA - Junari, Junari; Fitriani, Farida (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
Sociodrama methods play an important role in increasing student creativity because their used can help students in the learning process and was expected to increase creativity. But in reality there are still teachers who are not creative in teaching such as lecture learning methods and questions and answers. The formulation of the problem in this study was. This research used quantitative methods with 24 subjects. Data collection techniques used Questionnaire as the main method, observation as a step to find information directly while the documentation as a support method. Data analysis techniques used the chi square. Based on the results of data analysis in which X2 > X2-table was 10.757 > 9488 with a significance level of 5% in accordance with data analysis that has been obtained through research used the chi square formula, it turns out that the null hypothesis (H0) proposed was rejected and alternative hypothesis (Ha) was accepted, then the results of data analysis in this study are stated to be Significant. Thus it can be concluded that “There was The Effect of Sociodrama Method Towards Students’ Creativity Class XI in Indonesian Language Subjects at Al-Azhar Islamic High School West Lombok in Academic Year 2019/2020.